Proteolytic fragmentation of inositol 1,4,5‐trisphosphate receptors: a novel mechanism regulating channel activity? - Wang, Liwei (J Physiol, 2015)
Inositol 1,4,5‐trisphosphate receptors (IP(3)Rs) are a family of ubiquitously expressed intracellular Ca(2+) release channels. Regulation of channel activity by Ca(2+), nucleotides, phosphorylation, protein binding partners and other cellular factors is thought to play a major role in defining the specific spatiotemporal characteristics of intracellular Ca(2+) signals. These properties are, in turn, believed pivotal for the selective and specific physiological activation of Ca(2+)‐dependent effectors. IP(3)Rs are also substrates for the intracellular cysteine proteases, calpain and caspase. Cleavage of the IP(3)R has been proposed to play a role in apoptotic cell death by uncoupling regions important for IP(3) binding from the channel domain, leaving an unregulated leaky Ca(2+) pore. Contrary to this hypothesis, we demonstrate following proteolysis that N‐ and C‐termini of IP(3)R1 remain associated, presumably through non‐covalent interactions. Further, we show that complementary fragments of IP(3)R1 assemble into tetrameric structures and retain their ability to be regulated robustly by IP(3). While peptide continuity is clearly not necessary for IP(3)‐gating of the channel, we propose that cleavage of the IP(3)R peptide chain may alter other important regulatory events to modulate channel activity. In this scenario, stimulation of the cleaved IP(3)R may support distinct spatiotemporal Ca(2+) signals and activation of specific effectors. Notably, in many adaptive physiological events, the non‐apoptotic activities of caspase and calpain are demonstrated to be important, but the substrates of the proteases are poorly defined. We speculate that proteolytic fragmentation may represent a novel form of IP(3)R regulation, which plays a role in varied adaptive physiological processes. [Image: see text]